DETERMINANTS OF GREEN PURCHASE INTENTION OF FOOD PRODUCT CONSUMERS IN MEDAN CITY - Okto Rikiko Al Leonardo Dago; Syaifuddin Syaifuddin; Fajar Rezeki Ananda Lubis (Yayasan Nuraini Ibrahim Mandiri, 2026)
The large amount of plastic packaging used for food packaging must be considered for environmental health. Plastic food packaging has a significant negative impact on environmental degradation. Therefore, this study examines the determinants of green purchasing intentions among food consumers in Medan. This study used a quantitative method. The analysis was conducted using Secure Modeling (SEM) using the Smart-PLS version 3.0 application program. The researchers took a sample of 390 people. The results showed that Perceived Consumer Effectiveness (PCE) has a positive and significant influence on green purchasing intentions in Medan. Therefore, it can be concluded that Perceived Consumer Effectiveness is very important to be implemented in Medan to make the city healthier and also improve purchasing intentions.